Answer:
See Below.
Explanation:
The first three terms of an A.P is equivalent to the first three terms of a G.P.
We want to show that this is only possible if r = 1 and d = 0.
If a is the initial term and d is the common difference, the A.P. will be:
![a, a+d, \text{ and } a+2d](https://img.qammunity.org/2022/formulas/mathematics/high-school/mj6lenp4lxkxxttkyrtclm2fofvq6e9wni.png)
Likewise, for the G.P., if a is the initial term (and it does not equal 0) and r is the common ratio, then our sequence is:
![a, ar,\text{ and } ar^2](https://img.qammunity.org/2022/formulas/mathematics/high-school/jgd7s4j5ybyaw39xz7zevcs6woxtce17vf.png)
The second and third terms must be equivalent. Thus:
![a+d=ar\text{ and } a+2d=ar^2](https://img.qammunity.org/2022/formulas/mathematics/high-school/77rxj8tce6xzijzhu6csvtx4ye1i1u8t27.png)
We can cancel the d. Multiply the first equation by -2:
![-2a-2d=-2ar](https://img.qammunity.org/2022/formulas/mathematics/high-school/vpajflqsstteajvaz442g92z7qucwcnzfj.png)
We can now add this to the second equation:
![(a+2d)+(-2a-2d)=(ar^2)+(-2ar)](https://img.qammunity.org/2022/formulas/mathematics/high-school/vgykm7xn1rlxge0ozfq979b0mxmzhjmptb.png)
Simplify:
![-a=ar^2-2ar](https://img.qammunity.org/2022/formulas/mathematics/high-school/9is1b7ueylkdp4ghr3eger9a94k4rgyc1k.png)
Now, we can divide both sides by a (we can do this since a is not 0):
![-1=r^2-2r](https://img.qammunity.org/2022/formulas/mathematics/high-school/6rgo1fmqu9wxuocgzovlmkwcmy66kqkmtj.png)
So:
![r^2-2r+1=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/ax3j7zj7ctvhz10lqkgf2qzr5bbo6gw6de.png)
Factor:
![(r-1)^2=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/esd9looin928roj7evcjmayf00por5p3eq.png)
Thus:
![r=1](https://img.qammunity.org/2022/formulas/mathematics/high-school/apjegvnbj961af1grg8j35tkxpvpth9cbz.png)
The first equation tells us that:
![a+d=ar](https://img.qammunity.org/2022/formulas/mathematics/high-school/k50qqzd87hkyo5jgyos4tlarutrs431xjy.png)
Therefore:
![a+d=a(1)\Rightarrow a+d=a](https://img.qammunity.org/2022/formulas/mathematics/high-school/q69i41tldxqb6us6h4hb2xg55rwu9sw5k5.png)
Hence:
![d=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/r45f5lc4cvb90jlzfp66ky1nmz65s4btew.png)
Q.E.D.